Efficacy and safety of ofatumumab in recently diagnosed, treatment-naive patients with multiple sclerosis: Results from ASCLEPIOS I and II - Gärtner, Jutta; Hauser, Stephen L; Bar-Or, Amit; Montalban, Xavier; Cohen, Jeffrey A; Cross, Anne H; Deiva, Kumaran; Ganjgahi, Habib; Häring, Dieter A; Li, Bingbing; Pingili, Ratnakar; Ramanathan, Krishnan; et al. (Multiple sclerosis, 2022)
In the phase III ASCLEPIOS I and II trials, participants with relapsing multiple sclerosis receiving ofatumumab had significantly better clinical and magnetic resonance imaging (MRI) outcomes than those receiving teriflunomide. To assess the efficacy and safety of ofatumumab versus teriflunomide in recently diagnosed, treatment-naive (RDTN) participants from ASCLEPIOS. Participants were randomized to receive ofatumumab (20 mg subcutaneously every 4 weeks) or teriflunomide (14 mg orally once daily) for up to 30 months. Endpoints analysed post hoc in the protocol-defined RDTN population included annualized relapse rate (ARR), confirmed disability worsening (CDW), progression independent of relapse activity (PIRA) and adverse events. Data were analysed from 615 RDTN participants (ofatumumab: = 314; teriflunomide: = 301). Compared with teriflunomide, ofatumumab reduced ARR by 50% (rate ratio (95% confidence interval (CI)): 0.50 (0.33, 0.74); < 0.001), and delayed 6-month CDW by 46% (hazard ratio (HR; 95% CI): 0.54 (0.30, 0.98); = 0.044) and 6-month PIRA by 56% (HR: 0.44 (0.20, 1.00); = 0.049). Safety findings were manageable and consistent with those of the overall ASCLEPIOS population. The favourable benefit-risk profile of ofatumumab versus teriflunomide supports its consideration as a first-line therapy in RDTN patients.ASCLEPIOS I and II are registered at ClinicalTrials.gov (NCT02792218 and NCT02792231).